KRITIK SANAD DAN MATAN HADITS-HADITS MASYHUR DI KALANGAN PARA DA’I: Hadits Rajab Bulan Allah, Rasulullah Saw Terlahir Sudah Dikhitan, dan Menuntut Ilmu ke Negeri China - Evalinda, Evalinda; Ghulam Nazih, Abdullah; Marwan, Andi; Wulansari, Intan; Nurani, Dewi (Moderation | Journal of Islamic Studies Review, 2025)
The Prophet Muhammad's Hadiths are one of the primary sources of Islamic teachings, necessitating meticulous verification to preserve their authenticity. This study examines the sanad and matan criticism of popular hadiths among preachers, focusing on three: the sanctity of the month of Rajab as "Allah's month," the miraculous birth of the Prophet Muhammad circumcised, and the encouragement to seek knowledge even to China. Using a qualitative descriptive-analytical approach, this research evaluates the authenticity of these hadiths through classical and modern references. The results indicate that these hadiths are classified as weak (dha'if) or fabricated (maudhu’) due to critical flaws in their chains of transmission and inconsistencies in their texts. For instance, the hadith on Rajab conflicts with Quranic and authentic prophetic narratives, and the claim of the Prophet’s circumcised birth lacks credible supporting evidence. The study underscores the importance of rigorous sanad and matan analysis to ensure the preservation of Islamic teachings, guiding preachers and society toward reliable sources.